PRECONDITIONS FOR ENHANCING SOCIO-EDUCATIONAL ASSISTANCE TO INDIVIDUALS SERVING NON-CUSTODIAL SENTENCES - Žukauskienė, Lilia; Virsilas, Vaidas; Farbring, Carl Ake (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper focuses on the issue of socio-educational assistance to people prone to criminal behavior, unrelated to the use of psychoactive substances, and serving non-custodial sentences in the Probation Department of Klaipėda Regional Probation Service. It comments on the results of the behavioural correction programme Behaviour-Conversation-Change (BCC) applied to the individuals serving non-custodial sentences. The research was based on the quantitative research strategy. The participants of the research were individuals prone to criminal behavior, unrelated to the use of psychoactive substances, and serving non-custodial sentences in the Probation Department of Klaipėda Regional Probation Service. In the period from 2012 to 2017, 233 respondents took part in the research. The changes in the respondents' motivation were recorded by means of the University of Rhode Island Change Assessment (URICA) 32-item measure, designed to evaluate four key components: precontemplation, contemplation, action, and maintenance (McConnaughy, Prochaska, Velicer, 1983). The changes were evaluated at the beginning and at the end of the programme. As proved by the findings, the impact of the Behaviour-Conversation-Change programme was positive at the precontemplation and the action stages. The results achieved in the application of the Behaviour-Conversation-Change programme meaningfully differed, given the officers' approach to the programme.